PENELITIAN PENGGUNAAN BERBAGAI BAHAN STABILISASI TANAH UNTUK PERKERASAN JALAN - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Indonesia has various of soils properties, therefore not all soils in Indonesia has fullfill soil’s standard of bearing capacity in order to be suitable for road base of pavement. To fullfill specification of bearing capacity for road base of pavement needed to use soil stabilisation for soil that can use. There are variety of soil stabilisations type within different area in Indonesia i.e RRP, ESC, Phospogypsum, lime, cement,etc The characteristics of soil stabilisation perfomance was tested by laboratory, there are three types of soil stabilisation characteristics that use in three types of soils, are : Ronald Road Packer (RRP) 2-3-5 Special, Osaka Expansive Soil Compound (ESC) and Phospogypsum. The RRP and Phospogypsum as an organic soil stabilisation which function as a catalyst, improving CBR and density not too high, it reveals that the type of soil stailisation from pozzoland is proved CBR and density increase quicker and higher than the type from anorganic, therefore soil stabilisation materials from pozzoland is better to meet standard for road base of pavement.